Optimal discretionary policy and uncertainty about inflation persistence - Richhild Moessner (European Central Bank (ECB), 2005)
This paper studies optimal discretionary policy with parameter uncertainty about inflation inertia. Optimal policy rules and impulse responses are presented within a hybrid New-Keynesian model estimated for the euro area by Smets (2003). We find that it may be optimal for policy to respond more aggressively to cost-push shocks and real interest rate shocks in the presence of uncertainty about inflation inertia, depending on the form of the central bank's objective function. Moreover, in the cases where optimal policy is not certainty equivalent, we find that inflation returns slightly more gradually to equilibrium following a shock when the degree of inflation inertia is uncertain.
Keywords: E52; E58; 330; Inflation persistence; monetary policy; uncertainty; Inflation; Geldpolitik; Risiko; Theorie